2013
DOI: 10.4049/jimmunol.1300847
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Receptors for C3a and C5a Modulate Stability of Alloantigen-Reactive Induced Regulatory T Cells

Abstract: CD4+Foxp3+ regulatory T cells (Treg) are critical regulators of immune homeostasis and self-tolerance. Whereas thymic-derived or natural Treg (nTreg) stably express Foxp3, adaptive or induced Treg (iTreg) generated from peripheral CD4 T cells are susceptible to inflammation-induced reversion to pathogenic effector T cells (Teff). Building upon our previous observations that T cell-expressed receptors for C3a (C3aR) and C5a (C5aR) drive Th1 maturation, we tested the impact of C3aR/C5aR signaling on induction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
89
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 25 publications
5
89
1
Order By: Relevance
“…Overwhelming evidence has accumulated that C5aR1 activation regulates CD4 + T cell survival, proliferation, and differentiation into Th1 (35), Th2 (36), or Th17 (70-72) effector cells, as well as induced (31,70,73) and natural (57) regulatory CD4 + T cells. However, conflicting results exist about whether such regulation is driven primarily by the impact of C5a on APC activation or whether C5a can directly modulate T cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…Overwhelming evidence has accumulated that C5aR1 activation regulates CD4 + T cell survival, proliferation, and differentiation into Th1 (35), Th2 (36), or Th17 (70-72) effector cells, as well as induced (31,70,73) and natural (57) regulatory CD4 + T cells. However, conflicting results exist about whether such regulation is driven primarily by the impact of C5a on APC activation or whether C5a can directly modulate T cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the plasma concentration of C5a was significantly lower in KD patients than that in febrile controls. This decrease in plasma level of C5a might have resulted from rapid combination with C5aR in peripheral blood (20). It has also been postulated that decreased levels of C5a may protect against the inflammatory response (21).…”
Section: Discussionmentioning
confidence: 99%
“…Data published in 2013 indicate that complement also regulates Treg induction, function, and stability (12,30) (Figure 2). Our group showed that peripheral, murine, natural regulatory T cells (nTregs) express C3aR and C5aR and that signaling through these receptors inhibits Treg function (11).…”
Section: Links Between Complement and Adaptive Immunitymentioning
confidence: 98%
“…Mechanisms involve C3a/C5a-induced phosphorylation of AKT and, as a consequence, phosphorylation of the transcription factor Foxo1, which results in lowered nTreg Foxp3 expression. Two additional sets of data showed that genetic deficiency or pharmacologic blockade of C3aR/C5aR signaling augments murine-induced regulatory T cell (iTreg) generation, stabilizes Foxp3 expression, and resists iTreg conversion to IFN-g/TNF-a-producing effector T cells (12,30). Pharmacologic antagonists to human C3aR and C5aR also augment in vitro generation and stability of human iTreg from naïve precursors (12,30).…”
Section: Links Between Complement and Adaptive Immunitymentioning
confidence: 99%